Personality, gender, and type of school as factors affecting membership in voluntary associations of fourth year high school students in Poblacion, Miag-ao, Iloilo - Galvan, Teresa Angela Morcilla (1995.)
The importance of the various voluntary association in the development of students as adolescents is one of the bases for the study to materialize. This is a study on how factors of personality, gender, and type of school could affect membership in voluntary associations of fourth year high school students in Poblacion Miag-ao. The three factors were considered to affect membership in the two types of voluntary associations: (1)Personal Interest Groups; and (2)Social Service Groups. The objectives of the study were: to find out various reasons why students join these voluntary associations; To find out if personality affects membership in voluntary associations; To find out if gender affects membership in voluntary associations; and lastly, to find out if type of school affects membership in voluntary associations. The researcher hypothesized that factors of personality, gender, and type of school does not significantly affect membership in voluntary associations. Results of the study will help the students in knowing what could affect their membership in organizations they engage in. The EPPS (Edwards Personal Preference Schedule) was used to measure personality of the students and a questionnaire was used to find out relevant informations such as gender, type of school, and membership of students on the two types of voluntary associations. The instruments were administered to 82 male and female fourth year high school students, as respondents of the study, coming from Marillac Academy and Southern Iloilo Polytechnic High School which represent the sectarian and non-sectarian types of school respectively. With the use of Categorical Modeling Procedures and as provided by SAS (Statistical Analyses System) software, results have shown that factors of personality, and type of school seem to significantly affect membership in voluntary associations; however, gender does not seem to significantly affect membership in voluntary associations.
Thesis (Undergraduate, Bachelor of Arts in Psychology-Management) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Students, High School -- Miagao, Iloilo